Age-related Patterns of Vestibular Dysfunction in Dizziness and Imbalance: A Review of Vestibular Testing Results Among 1, 116 Patients. Issue 6 (July 2021) - Nimmo, Zachary M.; Hwa, Tiffany P.; Naples, James G.; Shah, Ravi; Brant, Jason A.; Eliades, Steven J.; Bigelow, Douglas C.; Ruckenstein, Michael J.
Abstract : Objective: To characterize differences in vestibular testing results among patients presenting with balance-related complaints; to stratify patterns of testing abnormalities by age. Study Design: Retrospective chart review. Setting: Academic Balance Center at a Tertiary Referral Center. Patient Population: All patients who underwent vestibular testing in a 1-year period from 2017 to 2018. Main outcome measure: Balance function test results. Results: We reviewed 1, 116 patients with age ranging from 11 to 94 years, including 521 patients ≥60 years. Most patients had at least 1 abnormal result, with only 21% of patients ≥60 years and 43% of patients <60 years yielding no test abnormalities ( p  < 0.001). Among 754 individuals with abnormal testing results, caloric testing did not show any significant difference between age groups. Patients ≥60 years of age were more likely to demonstrate abnormalities on saccadic and horizontal tracking eye movements ( p  < 0.01; sacc 20.8% vs 6.3%; HT 9.2% vs 4.7%), as well as positional and Dix-Hallpike testing with videonystagmography ( p  < 0.001; pos 52.3% vs 37.5%, DH 14.4% vs 6.8%). On computerized dynamic posturography, there were significantly more abnormal composite scores in the older group for both sensory organization and motor control testing ( p  < 0.001; SOT 31.8% vs 8.8%, MCT 7.6% vs 1.8%). Conclusion: Among patients presenting balance-related complaints, a majority demonstrate at least one abnormality on vestibular testing. While caloric abnormalities occur across the life span, patients ≥60 years of age are more likely to have abnormal results in random saccades, positional, Dix-Hallpike testing, and posturography, with greater effect sizes in tests of central function. While the causes of imbalance and vertigo remain multifactorial, vestibular dysfunction can be considered a major contributor to balance dysfunction in the elderly population and should be thoroughly evaluated. Abstract : Supplemental Digital Content is available in the text